SYAIR MAMBANG JAUHARI: TELAAH STRUKRURAL-SEMIOTIK - Maizar Karim (Center of Language and Cultural Studies, 2014)
Syair Mambang Jauhari (Mambang Jauhari verse) is one of the traditional Malay Literacy works. The components built in SMJ indicate closed and functional relationship. The components of rhythm, rhyme, line, and couplet function to struggle narrative structure and total meaning of the text for the society. The components of plot, background, point of view, form, theme, message, and integration have capacity to organize, form and maintain the relationships among the components inducing integration, strong structure, and meaning in the SMJ. The most dominant meaning of SMJ is that in creating the harmony in life, it is better to start from creating the micro-cosmos harmony among individuals and continue to macro-cosmos involving harmony in the social life, cultural life, political life, harmony in economic life, and in defense.